Justice or Controversy? The Case for Chemical Castration in the Republic of Kosovo’s Legal Framework - Alban Kryezi; Vedije Ratkoceri (Faculty of Law, Sriwijaya University, Indonesia, 2025)
This study evaluates a group of citizens’ attitudes in the Republic of Kosovo toward the potential inclusion of chemical castration in the Criminal Code as a punitive measure against child sexual abusers. Although chemical castration is not currently part of the Republic of Kosovo’s legal framework, growing public concern over increasing cases of child sexual abuse has brought this controversial measure into public and legal discourse. Using a survey-based methodology, the research analyses responses from a demographically diverse group, predominantly composed of young and educated individuals. The findings reveal widespread concern regarding the prevalence of sexual abuse against children. There is a high level of awareness and significant public support for chemical castration, with many respondents viewing it as an effective and preventive measure against sexual violence. However, ethical concerns related to human rights and reproductive health were also raised. Although few respondents reported direct knowledge of child victims, the study highlights several barriers to reporting such crimes, including inadequate institutional and familial support, social stigma, and prevailing conservative attitudes. Overall, the study offers valuable insights for Kosovo’s institutions to enhance their strategies in combating child sexual abuse. Understanding public opinion on chemical castration can inform the development of future legal and policy initiatives in this sensitive area.